Agarwood in the forest community and its potential depletion in West Papua - Destri; Zaenal Mutaqien; Andes Hamuraby Rozak (Foresty Faculty of Hasanuddin University, 2020)
Agarwood or eaglewood is a trading name of a solid resin from the two genera Aquilaria and Gyrinops which belongs to the Thymeleacea. The declining population of agarwood in natural forests placed the commodity regulated in Appendix II of the Convention on International Trade in Endangered Species (CITES). Indonesia as one of the habitats of those two genera and also the main exporting country of agarwood has an interest in ensuring the sustainability of agarwood. This study aims to provide an updated habitat of agarwood-producing trees and to estimate the potential density of the agarwood species. Research conducted in the forest of Natural Tourism Park of Beriat, West Papua, showed that Aquilaria filaria grows well in the forest. Five adult individuals were found in karst forest where 72% were dominated by small trees (DBH <20 cm). In terms of forest communities, Aquilaria's basal area reaches 1.9% of the total basal area and has a low importance value of 0.016 in the first dimension of Principal Component Analysis (PCA). The overall potential for agarwood-producing trees was estimated to be only around 2.50 and 2.89 for tree and seedling per hectare, respectively. The potential density is decreased when compared to the estimated density carried out 20 years ago which was estimated at around 4.33 trees per hectare. Efforts to protect agarwood, one of which is by determining trade quotas, need to be carried out optimally in order to minimize the decline in agarwood populations in their natural forests.